İslam hukuku ve Roma hukukunda genel hukuk prensiplerinin mukayesesi - Kurt, İrem (My University, 2017)
İslam ve Roma hukukunda benzeyen genel hukuk prensipleri bir çok çalışmaya konuolmuştur. ABSTRACT Certain Oriental scholars, are asserting the origins of islamic legal principles inRoman-Byzantinian law on the basis of some resemblances between some qawaid-i kulliyyaand Roman law principles, namely regulae iuris.
Keywords: Asl; Corpus İuris Civilis; Corpus İuris Civils; Hukuk; Hukuk, Karşılaştırmalı; İslam; İslam dini; Kaide; Kanon; Karşılaştırma; Karşılaştırna; Kıyas; Maxim; Orientalism; Oryantalizm; Qaida; Qıyas; Regula; Roma; SüryanîRoma Hukuk Kitabı; Syrian-RomanLaw Book